2016
DOI: 10.1111/ter.12196
|View full text |Cite
|
Sign up to set email alerts
|

The Cretaceous–Palaeogene boundary at Gorgonilla Island, Colombia, South America

Abstract: The discovery of a new Cretaceous/Palaeogene (K/Pg) bathyal marine sequence on Gorgonilla Island, SW Colombia, extends the presence of Chicxulub impact spherule deposits to the Pacific region of northern South America and to the Eastern Pacific Ocean. The Gorgonilla spherule layer is approximately 20 mm thick and consists of extraordinarily well-preserved glass spherules up to 1.1 mm in diameter. About 70-90% of the spherules are vitrified, and their chemical composition is consistent with Haiti (Beloc) impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
1
20
2
Order By: Relevance
“…As with the Haitian tektites, the Ca/K values (derived from 37 Ar/ 39 Ar data) of Gorgonilla samples display a large range both between and within individual tektites. This is consistent with the observations of Bermúdez et al (2016) from Gorgonilla, and of several electron probe microanalysis (EPMA) studies (Izett et al, 1991;Sigurdsson et al, 1991) of Haitian tektites, showing that individual tektites commonly contain mixtures of compositionally distinct glasses. Comparing plateau ages with integrated plateau values of Ca/K shows no correlation, verifying that the spherules of diverse composition were cogenetic, and that the Cainterference corrections (for reactor-produced 36 Ar and 39 Ar) are accurate.…”
Section: New Data and Their Implications 40 Ar/ 39 Ar Geochronologysupporting
confidence: 90%
See 2 more Smart Citations
“…As with the Haitian tektites, the Ca/K values (derived from 37 Ar/ 39 Ar data) of Gorgonilla samples display a large range both between and within individual tektites. This is consistent with the observations of Bermúdez et al (2016) from Gorgonilla, and of several electron probe microanalysis (EPMA) studies (Izett et al, 1991;Sigurdsson et al, 1991) of Haitian tektites, showing that individual tektites commonly contain mixtures of compositionally distinct glasses. Comparing plateau ages with integrated plateau values of Ca/K shows no correlation, verifying that the spherules of diverse composition were cogenetic, and that the Cainterference corrections (for reactor-produced 36 Ar and 39 Ar) are accurate.…”
Section: New Data and Their Implications 40 Ar/ 39 Ar Geochronologysupporting
confidence: 90%
“…1) overlies mafic and ultramafic basement rocks that form part of the Caribbean plateau, generated by the present Galapagos hotspot in the mid Cretaceous (Kennan and Pindell, 2009). It was located at 2000-3000 km southwest of the Chicxulub crater and represents a bathyal depth deposit (Bermúdez et al, 2016). Exposed near the southern tip of Gorgonilla Island, the section comprises ~40 m of interbedded tuffaceous sandstones and marls, with an ~20-mm-thick bed of normal-size-graded spherules occurring in mid-section ( Fig.…”
Section: Geologic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowe et al reported the largest impact glass spherule beds of the Archean Barberton Greenstone Belt in South Africa (Lowe et al, 2003(Lowe et al, , 2014Hofmann et al, 2006). The reports show important evidence of the occurrence of glass spherules, which may be impact-related in the K-Pg boundary deposits of Denerara Rise, Western Atlantic (Schulte et al, 2009) and Gorgonilla Island, Colombia, South America (Bermúdez et al, 2015). Spheres of transparent brown glass on the surface of the Chelyabinsk meteorite were observed (Galimov et al, 2013).…”
Section: Cosmic Spherules--glass Spherules and Fragmentsmentioning
confidence: 99%
“…Rise) within about one hour of the impact (Alvarez et al, 1995;MacLeod et al, 2007). In almost all shallower-water successions where spherules are recorded (e.g., New Jersey (Olsson et al, 1997), Colombia (Bermúdez et al, 2016) Rise records an in-situ, graded bed that may have taken approximately one month to accumulate (allowing for the time to settle through the water column). Belcher (2009) indicates that the heat provided by the spherules to the surface was <325°C, lasting only for a very short period of time.…”
Section: Accepted Manuscriptmentioning
confidence: 99%